Safety evaluation of styrax liquidus from the viewpoint of genotoxicity and mutagenicity. (24th December 2016) - Charehsaz, Mohammad; Reis, Rengin; Helvacioglu, Sinem; Sipahi, Hande; Guzelmeric, Etil; Acar, Ebru Turkoz; Cicek, Gamze; Yesilada, Erdem; Aydin, Ahmet
Abstract: Ethnopharmacological relevance: Styrax liquidus is a resinous exudate (balsam) obtained from the wounded trunk of the Liquidambar orientalis Mill. (Hamamelidaceae). Styrax has been used for treatment of various ailments in Turkish folk medicine such as skin problems, peptic ulcers, nocturnal enuresis, parasitic infections, antiseptic or as expectorant. Aim of study: In spite of frequent use of styrax in Turkish folk medicine as well as once as a stabilizer in perfumery industry, negative reports have been noticed by the international authority for restriction its use based on some limited evidences from an in vitro study. The aim of the present study was to evaluate the genotoxic and cytotoxic potential of styrax and its ethanolic extract using in vivo and in vitro assays, as well as an antimutagenic assay and also to determine its phenolic constituents with chromatographic analysis. Materials and methods: In vitro mutagenicity and antimutagenicity of styrax and its ethanolic extract were evaluated by Ames test performed on Salmonella TA98 and TA100 strains with and without metabolic activation (10– 30, 000 µg/plate). The genotoxicity was also studied in vivo by chromosomal aberrations assay on bone marrow of Balb C mice with different its concentrations (500–2000 mg/kg body weight). Cytotoxicity has been evaluated by the MTT assay using L929 cell line. Its phenolic constituents were determined by HPLC analysis. Results: Genotoxicological investigations of styrax or its ethanolic extract showed that none of the tested concentrations induced a significant increase in the revertant number of TA98 and TA100 strains with or without metabolic activation, indicating no mutagenicity to the tested strains. Also results indicated that up to 2000 mg/kg body weight, styrax is not genotoxic in mammalian bone marrow chromosome aberration test in vivo . In cytotoxicity study, the IC50 values of styrax and its ethanolic extract were found to be 50.22±1.80 and 59.69±11.77 µg/mL, respectively. Among the studied reference standards the major phenolic acids in styrax balsam was found to be p-coumaric acid (2.95 mg/g), while in its ethanolic extract not only p-coumaric acid (11.46 mg/g), but also gallic acid (1.60 mg/g) were found to the main components. Conclusion: The findings of the present study provide scientific basis to the safety of styrax from the viewpoint of genotoxicity risk, and in fact, it was found to be beneficial against genotoxicity. Graphical abstract: